Regulatory mechanism of MeGI on sexuality in Diospyros oleifera - Mai, Yini; Sun, Peng; Suo, Yujing; Li, Huawei; Han, Weijuan; Diao, Songfeng; Wang, Liyuan; Yuan, Jiaying; Wang, Yiru; Ye, Lingshuai; Zhang, Yue; Li, Fangdong; et al. (Frontiers in Plant Science, 2023)
Dioecy system is an important strategy for maintaining genetic diversity. The transcription factor MeGI, contributes to dioecy by promoting gynoecium development in Diospyros lotus and D. kaki. However, the function of MeGI in D. oleifera has not been identified. In this study, we confirmed that MeGI, cloned from D. oleifera, repressed the androecium development in Arabidopsis thaliana. Subsequently, chromatin immunoprecipitation-sequencing (ChIP-seq), DNA affinity purification-sequencing (DAP-seq), and RNA-seq were used to uncover the gene expression response to MeGI. The results showed that the genes upregulated and downregulated in response to MeGI were mainly enriched in the circadian rhythm-related and flavonoid biosynthetic pathways, respectively. Additionally, the WRKY DNA-binding protein 28 (WRKY28) gene, which was detected by ChIP-seq, DAP-seq, and RNA-seq, was emphasised. WRKY28 has been reported to inhibit salicylic acid (SA) biosynthesis and was upregulated in MeGI-overexpressing A. thaliana flowers, suggesting that MeGI represses the SA level by increasing the expression level of WRKY28. This was confirmed that SA level was lower in D. oleifera female floral buds than male. Overall, our findings indicate that the MeGI mediates its sex control function in D. oleifera mainly by regulating genes in the circadian rhythm, SA biosynthetic, and flavonoid biosynthetic pathways.